2012
DOI: 10.5999/aps.2012.39.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports of Adipose-derived Stem Cell Therapy for Nasal Skin Necrosis after Filler Injection

Abstract: With the gradual increase of cases using fillers, cases of patients treated by non-medical professionals or inexperienced physicians resulting in complications are also increasing. We herein report 2 patients who experienced acute complications after receiving filler injections and were successfully treated with adipose-derived stem cell (ADSCs) therapy. Case 1 was a 23-year-old female patient who received a filler (Restylane) injection in her forehead, glabella, and nose by a non-medical professional. The day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 10 publications
1
34
0
1
Order By: Relevance
“…In the 13 flaps having clinical necrosis, this combined necrosis was found in 11 flaps. Our findings were consistent with the clinical presentations of HA embolism cases [6][7][8][9][10][11][12], which suggested that not only arterial occlusion but also venous occlusion was involved.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the 13 flaps having clinical necrosis, this combined necrosis was found in 11 flaps. Our findings were consistent with the clinical presentations of HA embolism cases [6][7][8][9][10][11][12], which suggested that not only arterial occlusion but also venous occlusion was involved.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study demonstrated that it was the accidental intra-arterial injection that caused the ischemia, rather than external vascular compression on distal perfusion [5]. Ischemia with subsequent skin necrosis mainly occurs in the glabella [6,7], nose [7][8][9][10][11][12], forehead [7,8], nasolabial fold [10], and cheek [13]. Moreover, intracranial artery embolism can lead to blindness caused by retinal artery occlusion and [10,11,13] has been sporadically reported to treat HA embolism-induced skin necrosis [14][15][16][17], however, well-designed case-control studies are required to verify the efficacy and safety of hyaluronidase before it can be used routinely in humans.…”
Section: Introductionmentioning
confidence: 99%
“…These outstanding features highlight the importance of cell therapy. Researchers in medical sciences believe that use of cell therapy, along with gene therapy, can influence the occurrence of diseases in the future (1,2).…”
Section: Contextmentioning
confidence: 99%
“…More caution has to be taken in patients with a history of bee allergy because hyaluronidase is considered to be one of the active components in bee venom [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. There are no reported anaphylactic reactions after subepidermal injections [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Guidelinesmentioning
confidence: 99%